2003
DOI: 10.1128/jvi.77.23.12753-12763.2003
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 Induction during Murine Gammaherpesvirus 68 Infection Leads to Enhancement of Viral Gene Expression

Abstract: The gamma subfamily of herpesviruses, including EpsteinBarr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV) or human herpesvirus 8 (HHV-8), are associated with tumors and lymphoproliferative disorders (29,43). Murine gammaherpesvirus 68 (MHV-68) is phylogenetically related to EBV and KSHV and provides major research advantages by forming plaques on cell monolayers and establishing productive lytic and latent infections in mice (10,(64)(65)(66). Unlike EBV and KSHV, MHV-68 readily establishes pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 74 publications
5
47
0
Order By: Relevance
“…COX catalyzes the oxidation of arachidonic acid to PGH 2 , which is then isomerized to biologically active eicosanoids and thromboxanes (1). Expression of COX-2 is activated in response to a wide variety of cytokines and inflammatory mediators as well as during virus infection (2)(3)(4)(5)(6)(7). One of the predominate products of COX enzymatic activity is PGE 2 and increased production of this prostaglandin has been shown to modulate the replication and infectivity of a number of viruses (7).…”
Section: Role Of Mapk In the Regulationmentioning
confidence: 99%
“…COX catalyzes the oxidation of arachidonic acid to PGH 2 , which is then isomerized to biologically active eicosanoids and thromboxanes (1). Expression of COX-2 is activated in response to a wide variety of cytokines and inflammatory mediators as well as during virus infection (2)(3)(4)(5)(6)(7). One of the predominate products of COX enzymatic activity is PGE 2 and increased production of this prostaglandin has been shown to modulate the replication and infectivity of a number of viruses (7).…”
Section: Role Of Mapk In the Regulationmentioning
confidence: 99%
“…To accomplish this, we used a protocol to produce UV light-inactivated gHV68 (UVgHV68), which has previously been shown to limit viral replication (34). Mice were again given FITC intratracheally on Day 0.…”
Section: Lytic Viral Replication Is Required For Exacerbation Of Fitcmentioning
confidence: 99%
“…Mock infections were 20 ml of saline. gHV68 was inactivated by exposure to ultraviolet (UV) light using a UV cross-linker set on 120,000 microjoules for four consecutive cycles as previously described (34).…”
Section: Viral Infectionmentioning
confidence: 99%
“…Previous studies have reported that production of COX-2 and PGE 2 modulates replication of human cytomegalovirus, gammaherpesvirus, and hepatitis B virus. [18][19][20] To investigate the possible mechanism(s) responsible for ASA-mediated down-regulation of HCV-RNA expression, we examined COX-2 activity, mRNA, and protein levels in ASAtreated HCV replicon cells. In this study, we found that 4 mM ASA treatment down-regulated COX-2 protein (Fig.…”
Section: Asa-mediated Down-regulation Of Hcv Expression Is Not Mediatmentioning
confidence: 99%